Alteplase for the treatment of acute ischemic stroke in patients with low National Institutes of Health Stroke Scale and not clearly disabling deficits (Potential of rtPA for Ischemic Strokes with Mild Symptoms PRISMS): Rationale and design. Issue 6 (August 2018) - Yeatts, Sharon D; Broderick, Joseph P; Chatterjee, Anjan; Jauch, Edward C; Levine, Steven R; Romano, Jose G; Saver, Jeffrey L; Vagal, Achala; Purdon, Barbara; Devenport, Jenny; Khatri, Pooja
Rationale: Over half of acute ischemic stroke patients have a low National Institutes of Health Stroke Scale of 0–5 and up to two-thirds may not appear clearly disabled at presentation. The efficacy of intravenous alteplase for the latter group is not known. Aim: Potential of rtPA for Ischemic Strokes with Mild Symptoms (PRISMS) was designed to evaluate the safety and efficacy of intravenous alteplase for the treatment of acute ischemic stroke with National Institutes of Health Stroke Scale 0–5 and without clearly disabling deficits. Sample size estimates: A maximum of 948 subjects were required to test the superiority hypothesis with 80% power, according to a one-sided 0.025 level of significance. Methods and design: PRISMS was a multicenter, randomized, double-blind, placebo-controlled phase 3b clinical trial. Patients were randomized to the active arm (intravenous alteplase standard dose of 0.9 mg/kg, up to a maximum of 90 mg, plus oral aspirin placebo) or the control arm (intravenous alteplase placebo plus active oral aspirin dose of 325 mg). Study outcome: The primary efficacy endpoint was favorable functional outcome, defined as a modified Rankin Scale score 0 or 1 assessed at 90-day postrandomization.